Global warming assessment suggests the endemic Brazilian kelp beds to be an endangered ecosystem. (June 2021) - Anderson, A.B.; Assis, J.; Batista, M.B.; Serrão, E.A.; Guabiroba, H.C.; Delfino, S.D.T.; Pinheiro, H.T.; Pimentel, C.R.; Gomes, L.E.O.; Vilar, C.C.; Bernardino, A.F.; Horta, P.; et al.
Abstract: Kelps are canopy-forming brown seaweed sustaining critical ecosystem services in coastal habitats, including shelter, nursery grounds, and providing food resources to a myriad of associated species. This study modeled the fundamental niche of Laminaria abyssalis along the Brazilian continental margin, an endemic species of the South Atlantic, to anticipate potential distributional range shifts under two contrasting scenarios of future environmental changes (RCP2.6 and RCP8.5). The model for fundamental niche predictions considering the "present scenario" has shown a wider potential area than the realized niche (i.e., the area where the species actually occurs) along the Brazilian coast. In both future scenarios, the models have shown niche erosion on the northern portion of the Brazilian coast and niche gains towards the south. In both scenarios, L. abyssalis populations tend to shift to deeper regions of the reef. The restricted range of occurrence (33, 000 km 2 ), intense anthropic activities along these beds (e.g., trawling fisheries, oil/gas mining, or removal for agricultural purposes) acting synergically with global warming, may drive this ecosystem to collapse faster than kelp species' ability to adapt. We propose to classify L. abyssalis as Endangered - (EN) under IUCN criteria, and highlight that long-term monitoring of kelp beds is an urgent need to develop effective conservation initiatives to protect such rare and invaluable ecosystem. Highlights: Global warming drives laminarian kelps distribution shifts. Anthropogenic climate change increases kelps niche shifts. Future scenario indicates niche erosion of Laminaria abyssalis populations. Climate change drives kelps vertical and horizontal distributional shifts.